Crowdsourcing as an Innovative Model in Public Policy Decision Making: Opportunities and Challenges - Sarjito, Aris; Mursidi, Mursidi (Universitas Hang Tuah, 2025)
Crowdsourcing has emerged as a transformative mechanism in public policy decision-making, enabling governments to leverage collective intelligence for more inclusive, transparent, and effective governance. This study explores the opportunities, challenges, and best practices of integrating crowdsourcing into policymaking. The research highlights how crowdsourcing enhances citizen participation, fosters transparency, and improves decision-making efficiency by providing diverse perspectives. However, key challenges such as misinformation, the digital divide, data security risks, and ethical concerns pose barriers to its effective implementation. To address these challenges, strategic frameworks are essential, including hybrid governance models, AI-driven data verification, and enhanced digital inclusivity policies. The study provides policy recommendations for optimizing crowdsourcing, emphasizing robust regulatory frameworks, stronger data protection laws, and equitable access to participation platforms. Furthermore, it identifies future research directions, including the potential of AI in refining crowdsourcing accuracy and cross-country comparative studies on best practices. As governments increasingly adopt digital governance models, crowdsourcing must be carefully managed to balance openness with accountability. By implementing structured strategies, policymakers can maximize the benefits of crowdsourcing while mitigating its risks, fostering a more democratic, transparent, and effective governance system.